EARLY NAXALITE MOVEMENT IN KERALA (1968-1976) : A STUDY ON THE ISSUES, CHALLENGES AND ALTERNATE APPROACHES - MANJUSHA.K.A (International Journal of Multidisciplinary Research, 2014)
As in states which had a tradition of communist politics, Kerala too witnessed the sound and fury of the naxalite movement in the 1960s and 70s. The naxalite movement in Kerala was more an intellectual phenomenon than political activism arising from any feudal social and economic order in the state. It is mainly based on the Maoist ideology and gains its strength through mobilizing the poor, unprivileged, discouraged and marginalized, especially in the tribal areas. The movement‟s root causes are located within India‟s numerous social and economic inequalities as well as environmental degradation. Without understanding the root causes, the state will not be able to solve the problem. This paper is divided into three parts and tries to give an extensive overview of the complex issue of the Naxalite conflict. Therefore the first part deals with the history of the movement in Kerala by describing its origin and development from 1968-1976 . Part two deals with the strategy and actions of the Naxalites and sets its focus on the root causes. The final part covers the causes for the failure of the movement and conclusion.